The Effect of Implementing Pre-Conference and Post-Conference on the Completeness of Nursing Care Documentation: A Systematic Review - Acep Yudi Wahyudi; Elsye Maria Rosa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Completeness of nursing care documentation is an important indicator of service quality and patient safety because it supports continuity of care, communication between shifts, and professional accountability. However, in clinical practice, documentation is often incomplete due to workload, time constraints, varying adherence to SOPs, and minimal feedback. Pre- and post-conferences, as a forum for structured briefings and evaluations, are seen as capable of organizing team communication flows and strengthening process discipline, thus potentially improving documentation completeness. To synthesize scientific evidence regarding the application of pre-conference and post-conference in nursing practice and their impact on the completeness of nursing care documentation. The study design was a systematic review with narrative synthesis. A literature search was conducted on Google Scholar, Scopus, and PubMed for articles published between 2011 and 2025, in Indonesian or English. Included studies were original research that evaluated the implementation of pre- and/or post-conferences for nurses or nursing teams in clinical settings and reported outcomes related to completeness of documentation or relevant process quality indicators. Selection was conducted through title/abstract screening and full-text assessment. Data were then standardized and synthesized descriptively due to heterogeneity in design, context, and measurement indicators. Eight studies met the inclusion criteria with varying designs, including case studies, descriptive studies, PDSA-based pilot studies, quasi-experimental, pre-experimental, and cross-sectional correlational studies. Thematic synthesis showed that pre-conferences play a role in establishing shared clinical perceptions, establishing priorities, and aligning care plans, resulting in more focused recording. While post-conferences serve to close the work cycle by evaluating and verifying completeness before the shift change. Studies that directly assessed documentation reported improved completeness after the implementation of pre- and post-conferences, while others demonstrated improved compliance with the handover/conference process and nurse performance as supporting mechanisms for documentation quality. Effective implementation appeared to be influenced by team leader leadership, clarity of SOPs and formats, practice-based training (e.g., role-play/simulation), and tiered supervision. Workload and time constraints, particularly at the end of the shift, were key barriers. Implementing pre- and post-conferences has the potential to improve the completeness of nursing care documentation by improving team communication processes, standardizing clinical priorities, and strengthening accountability before handover. A more consistent impact is likely to emerge when conferences are integrated into a quality control system that includes clear standard operating procedures (SOPs), training, supervision, and periodic documentation audits and feedback.